Handbook in Monte Carlo simulation : applications in financial engineering, risk management, and economics - Brandimarte, Paolo (Hoboken, New Jersey : John Wiley & Sons, 2014)
An accessible treatment of Monte Carlo methods, techniques, and applications in the field of finance and economics Providing readers with an in-depth and comprehensive guide, the Handbook in Monte Carlo Simulation: Applications in Financial Engineering, Risk Management, and Economics presents a timely account of the applicationsof Monte Carlo methods in financial engineering and economics. Written by an international leading expert in thefield, the handbook illustrates the challenges confronting present-day financial practitioners and provides various applicationsof Monte Carlo techniques to.
Part Four: Output Analysis and Efficiency ImprovementChapter Seven: Output Analysis; 7.1 Pitfalls in output analysis; 7.2 Setting the number of replications; 7.3 A world beyond averages; 7.4 Good and bad news; For further reading; References; Chapter Eight: Variance Reduction Methods; 8.1 Antithetic sampling; 8.2 Common random numbers; 8.3 Control variates; 8.4 Conditional Monte Carlo; 8.5 Stratified sampling; 8.6 Importance sampling; For further reading; References; Chapter Nine: Low-Discrepancy Sequences; 9.1 Low-discrepancy sequences; 9.2 Halton sequences.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finance -- Mathematical models; Economics -- Mathematical models; Monte Carlo method; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Economics -- Mathematical models; Finance -- Mathematical models; Monte Carlo method; Monte Carlo method; Electronic books; Electronic books